The Landscape of Civil Society Organizations in the Economy of Kosovo - Vllasaj, Kushtrim (International Journal of Engineering and Management Sciences, 2020)
Civil society organizations (CSOs) in the scientific literature have been studied broadly from various aspects such as cultural, political, social and economic. But as far as the last one is concerned, there is still a research gap because there is a lack of study about their contribution to economies under development, such as Kosovo, and which must be filled because of its importance. This paper tends to analyze the present situation of CSOs in Kosovo and their potential contribution to economic activity. Highlighting the activities, the structure and the place of these organizations in the economy will be the approach, in the beginning, to pave the way for further study of specific areas related to them. The methodology established contains analyses of secondary sources that are done by using data from the Ministry of Public Administration of Kosovo, Kosovar Index of Civil Society which is a regular report of the Kosovar Civil Society Foundation (KCSF), and other supplementary data. However, this will proceed after the scientific conceptual issues of CSOs and their place within the economy. Finally, the results show that civil society in Kosovo is very diverse with organizations in different sectors, and the economic activity sector consists of mostly agricultural NGOs.   In transition countries, CSOs are seen as an alternative that improves a particular sector. Thus far, there are over 10,000 organizations established in Kosovo, but relative studies suggest only 1000 to be active. Furthermore, their activity and contribution to economic development is little known so far, while the main problem of the economy remains unemployment.